PkM UJI KOMPETENSI KEAHLIAN SISWA JURUSAN TEKNIK OTOMOTIF ALAT BERAT DI SMK RIGOMASI BONTANG - Ahmad Yani (LPPM Universitas Bina Bangsa, 2021)
Expertise Competency Test (UKK) is part of government intervention in ensuring the quality of education in Vocational High School education units. One of the government's efforts to improve students' knowledge and skills, especially for Vocational High Schools, is by holding a skill competency test that determines student graduation. Competency testing is needed to determine a person's ability or competence according to professional standards. To be accepted to work in the world of work, a person must be competent, which is evidenced by, among other things, a competency certificate through a competency test. A person is said to have the competence (competent) in a particular field if he has the knowledge, skills, and attitudes to complete the job correctly by the demands of professionalism. The purpose of implementing this UKK is to measure the competency attainment of Rigomasi Vocational High School students at a certain level according to the expertise of heavy equipment automation engineering majors taken during the learning period at school